Regulation of appressorium development in pathogenic fungi. (August 2015) - Ryder, Lauren S; Talbot, Nicholas J
Highlights: Appressorium development is linked to cell cycle checkpoints controlling morphogenesis. Ras GTPase signalling acts upstream of cAMP and MAP kinase pathways for appressorium development. Melanin is not exclusively associated with appressorium turgor generation. . Septin-mediated actin re-modelling is essential for appressorium function. Focal secretion of effectors occurs during appressorium infection. Abstract : Many plant pathogenic fungi have the capacity to breach the intact cuticles of their plant hosts using specialised infection cells called appressoria. These cells exert physical force to rupture the plant surface, or deploy enzymes in a focused way to digest the cuticle and plant cell wall. They also provide the means by which focal secretion of effectors occurs at the point of plant infection. Development of appressoria is linked to re-modelling of the actin cytoskeleton, mediated by septin GTPases, and rapid cell wall differentiation. These processes are regulated by perception of plant cell surface components, and starvation stress, but also linked to cell cycle checkpoints that control the overall progression of infection-related development.